Urban Sprawl Mapping For Beach Tourism Suitability Using GIS-AHP Model In Kuantan District - Ahmad Azizul, Khalid (2023)
Urban sprawl has expanded as a result of urbanization's rapid growth, posing serious environmental and socioeconomic problems, particularly in areas with great natural resources, like coastal regions. With the help of a Geographic Information System (GIS) and the Analytic Hierarchy Process (AHP) model, this study seeks to solve the problem of urban sprawl and its effects on beach tourism appropriateness in the Kuantan District. The study makes use of GIS-based spatial analysis methods, land use/land cover maps, and remotely sensed data to accomplish this goal. The initial step entails using historical land cover data to identify and track the dynamics of urban spread in the Kuantan District. The amount and rate of urban expansion over time will be calculated using the urban sprawl index. The suitability elements for beach tourism will then be determined after a thorough literature review and professional consultation. Accessibility to beaches, environmental quality, infrastructure, and cultural relevance are a few examples of these variables. Weighing each aspect according to its importance will be done using the AHP model, a multi-criteria decision-making technique, to provide a thorough appropriateness index for beach tourism. To pinpoint regions where beach tourist potential has been compromised by urban sprawl, the GIS-AHP model will integrate the urban sprawl index with the beach tourism suitability index. The study will identify locations that are more vulnerable to the effects of urban growth and assess how suitable each zone in the Kuantan District is for beach tourism by superimposing these datasets. The research's conclusions will help urban planners, decision-makers, and tourist industry participants make wise choices about land use planning, urban development, and sustainable tourism management. To lessen the negative effects of urban growth on beach tourism, the study will help identify places that need specialized conservation and intervention techniques.